The Factors Affecting The Incidence Of Hyperuricemia On The Rejang Tribe In Bengkulu - Jumiyati Jumiyati; Tetes Wahyu Witradharma (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2020)
The Rejang tribe is partly living on the lowland and coastal coastline, the typical Rejang cooking tradition has been assimilated into the Minang and Malay cooking traditions. Malay people like to consume foods that are fatty, dining, oily and salty. Fish, beef, shrimp and nuts have purine content of 9-100 mg of purin/100 g of foodstuffs. One of the factors affecting hyperuricemia is the habit of consuming purine eating, it will result in gout disease. The purpose of this research is to determine the factors that influence the incidence of hyperuricemia on the Rejang tribe in Bengkulu. Design research is cross sectional. Rejang Group's research samples numbered 64 respondents. Data collected is the result of uric acid examination, gender, age, knowledge, consumption pattern, liquid consumption, BMI. The instruments used are questionnaires, eating consumption patterns using FFQ form, weight gained by weighing with digital scales. Data analysis using Chi-Square and multivariate tests using logistic regression test